The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10327-007-0028-6
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Plum pox virus through in vitro thermotherapy and shoot tip culture compared to conventional heat treatment in apricot cultivar Bebecou

Abstract: The effectiveness of in vitro thermotherapy (explants at 35-37°C for 20 days) in obtaining propagating material of apricot (Prunus armeniaca L.) cultivar Bebecou that is free of Plum pox virus (PPV) was compared to a conventional heat treatment technique (potted plants at 30-35°C for 8 weeks). An improved protocol for in vitro thermotherapy was combined with shoot tip culture. The protocol is 5.8 times more effective than conventional thermotherapy while taking half the time and is likely to have a high commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Although in vitro thermotherapy in combination with shoot tip excision proved to eliminate PPV effectively in apricot cv 'Bebecou' (Koubouris et al, 2007), the survival rate of the explants subjected to in vitro thermotherapy in that study barely reached to 28%. This result is inconsistent with our findings as a decline in survival was observed after prolonged incubation of microshoots to 37°C, implying that woody plants were sensitive to prolonged exposure to extreme high temperatures (Spiegel et al, 1995).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although in vitro thermotherapy in combination with shoot tip excision proved to eliminate PPV effectively in apricot cv 'Bebecou' (Koubouris et al, 2007), the survival rate of the explants subjected to in vitro thermotherapy in that study barely reached to 28%. This result is inconsistent with our findings as a decline in survival was observed after prolonged incubation of microshoots to 37°C, implying that woody plants were sensitive to prolonged exposure to extreme high temperatures (Spiegel et al, 1995).…”
Section: Discussionmentioning
confidence: 74%
“…In the case of apricot, thermotherapy was applied by several researchers (i.e., Koubouris et al, 2007;Křižan and Ondrušiková, 2009), however the potential of not only usage of different chemotherapeutic agents for chemotherapy but also application of various cryogenic methods for cryotherapy still needs to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Ram et al [ 33 ] found chemotherapy (30–40 mg L −1 2-thiouracil) followed by thermotherapy (38 °C, 30 days) was most effective in CVB eradication among the five antiviral chemicals tested. 2-thiouracil was also shown to be effective in eradicating LSV, TBV-L and CMV from lily [ 73 ], and PLRV from potato [ 34 ].…”
Section: Key Factors Affecting Success Of Virus Eradicationmentioning
confidence: 99%
“…Thermotherapy is the term used to refer to the application of a high temperature that generates unfavorable conditions for virus multiplication in the cells and effectively decreases the virus load in the shoot tips [9][10][11][12]. Among the established thermotherapybased methods typically used for virus elimination, combined in vitro thermotherapy with shoot tip culture, micrografting, electrotherapy, chemotherapy (especially using ribavirin), and shoot tip cryotherapy has been reported to be efficient for the eradication of different viruses from plants [8,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%